Domesticate in the Name of Islam - Yousif, Mariam (2013)
A Master of Arts thesis in Translation and Interpreting (English/Arabic/English) by Mariam Yusuf entitled, "Domesticate in the Name of Islam," May 2013. Thesis advisor is Dr. Said Faiq. Available are both hard and soft copies of the thesis.